PRIMA 2012: Principles and Practice of Multi-Agent Systems 15th International Conference, Kuching, Sarawak, Malaysia, September 3-7, 2012. Proceedings - Rahwan, Iyad.; Wobcke, Wayne; Sen, Sandip; Sugawara, Toshiharu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 15th International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2012, held in Kuching, Sarawak, Malaysia, in September 2012. The conference was collocated with the 12th Pacific Rim International Conference on Artificial Intelligence, PRICAI. The 17 revised full papers presented were carefully reviewed and selected from 42 submissions. The papers are organized in topical sections on foundations, auctions and negotiation, coalition formation and teamwork, norms and institutions, and applications.
foundations -- auctions and negotiation -- coalition formation and teamwork -- norms and institutions -- applications.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Software Engineering; e-Commerce/e-business.; Information Storage and Retrieval; User Interfaces and Human Computer Interaction